Precision Vaccine Development: Cues From Natural Immunity - Barman, Soumik; Soni, Dheeraj; Brook, Byron; Nanishi, Etsuro; Dowling, David J. (Frontiers in Immunology, 2022)
Traditional vaccine development against infectious diseases has been guided by the overarching aim to generate efficacious vaccines normally indicated by an antibody and/or cellular response that correlates with protection. However, this approach has been shown to be only a partially effective measure, since vaccine- and pathogen-specific immunity may not perfectly overlap. Thus, some vaccine development strategies, normally focused on targeted generation of both antigen specific antibody and T cell responses, resulting in a long-lived heterogenous and stable pool of memory lymphocytes, may benefit from better mimicking the immune response of a natural infection. However, challenges to achieving this goal remain due to gaps in our understanding of human immunity and full elucidation of infectious pathogenesis. In this review, we describe recent advances in the development of effective vaccines, focusing on how understanding the differences in the immunizing and non-immunizing immune responses to natural infections and correspond shifts in immune ontogeny are crucial to inform the next generation of infectious disease vaccines.